MATERNAL COMPLIANCE IN POSTPARTUM VISITS IN PULAU BULUH VILLAGE BULANG DISTRICT, BATAM CITY - Efilona Setri; Mohd. Faisyal Reza (Universitas Batam, 2020)
Background : According to the World Health Organization (WHO), maternal mortality is still quite high, every day around the world around 800 women die from complications during pregnancy, childbirth and the puerperium. In 2013, 289,000 women died during and after pregnancy, childbirth and the puerperium. Between 1990 and 2013, the global maternal mortality rate (i.e. the number of maternal deaths per 100,000 live births) decreased by only 2.6% per year. This figure is still far from the target of reducing the annual MMR (5.5%) needed to achieve the 5th MDG target (Andiani, and Retno, 2014). Method : The research objective was to determine the compliance of mothers in conducting postpartum visits. Result : Results of the Research on Maternal Compliance in Postpartum Visits Postpartum Visits in Pulau Buluh Village, Bulang District, Batam City It was found that maternal post-partum visits in Pulau Buluh Village consisted of 35 respondents, namely 19 respondents (54%) postnatal visits were obedient, and 16 respondents (46 %) postpartum visits are non-compliant Conclusion : It is known that 19 (54%) of the respondent's frequency distribution of Compliance Postpartum visits are complete and 16 (46%) respondents who are incomplete during postpartum visits